Optimizing the sensing performance of amperometric creatinine detection based on creatinine deiminase/Nafion®-nanostructured polyaniline composite film by mixture design method - Do, Jing-Shan; Chang, Yu-Hsuan (Sensors and actuators reports, 2023)
•Optimal conditions for preparing composite sensing films studied by mixture design.•Comparing with conventional method, the sensitivity of creatinine biosensor is promoted by 54.9%.•High selectivity of amperometric creatinine biosensor is obtained.•The fading fraction of creatinine biosensor is 6.60% for 240 times sensing. Nafion®-nanostructured polyaniline (nsPANi) composite film is prepared using cyclic voltammetry (CV) and immobilized with creatinine deiminase (CD) enzyme and is used to sense creatinine in a buffer phosphate solution. The conditions for preparing Nafion®-nsPANi composite film are optimized by using a mixture design for which the sensitivity is the response. The relationship between the sensitivity of the amperometric creatinine biosensor (y) and the normalized aniline concentration (Y1), HCl concentration (Y2) and scanning rate (Y3) is y = 119.44Y1 + 45.23Y2 + 100.93Y3 + 255.69Y1Y2 + 313.16Y1Y3 + 430.56Y1Y2Y3 The maximum sensitivity of an amperometric creatinine biosensor that is constructed using Nafion®-nsPANi composite film in 0.0943 M aniline, 0.9024 M HCl and using a scanning rate of 27.88 mV s − 1 is 2013.2 μA mM−1 cm−2, which is 54.9% better than the sensitivity of a conventional experimental technique. The amperometric creatinine biosensor is 6.60% less sensitive after sensing 0.15 mM creatinine 240 times. The amperometric creatinine biosensor incurs insignificant interference in 0.138 mM urea, 0.085 mM ascorbic acid (AA) and 5.54 mM glucose. [Display omitted]